Comparative Genomics Reveal a Flagellar System, a Type VI Secretion System and Plant Growth-Promoting Gene Clusters Unique to the Endophytic Bacterium Kosakonia radicincitans - Becker, Matthias; Patz, Sascha; Becker, Yvonne; Berger, Beatrice; Drungowski, Mario; Bunk, Boyke; Overmann, Jörg; Spröer, Cathrin; Reetz, Jochen; Tchuisseu Tchakounte, Gylaine V.; Ruppel, Silke (Frontiers in Microbiology, 2018)
The recent worldwide discovery of plant growth-promoting (PGP) Kosakonia radicincitans in a large variety of crop plants suggests that this species confers significant influence on plants, both in terms of yield increase and product quality improvement. We provide a comparative genome analysis which helps to unravel the genetic basis for K. radicincitans' motility, competitiveness and plant growth-promoting capacities. We discovered that K. radicincitans carries multiple copies of complex gene clusters, among them two flagellar systems and three type VI secretion systems (T6SSs). We speculate that host invasion may be facilitated by different flagella, and bacterial competitor suppression by effector proteins ejected via T6SSs. We found a large plasmid in K. radicincitans DSM 16656T, the species type strain, that confers the potential to exploit plant-derived carbon sources. We propose that multiple copies of complex gene clusters in K. radicincitans are metabolically expensive but provide competitive advantage over other bacterial strains in nutrient-rich environments. The comparison of the DSM 16656T genome to genomes of other genera of enteric plant growth-promoting bacteria (PGPB) exhibits traits unique to DSM 16656T and K. radicincitans, respectively, and traits shared between genera. We used the output of the in silico analysis for predicting the purpose of genomic features unique to K. radicincitans and performed microarray, PhyloChip, and microscopical analyses to gain deeper insight into the interaction of DSM 16656T, plants and associated microbiota. The comparative genome analysis will facilitate the future search for promising candidates of PGPB for sustainable crop production.